1988
DOI: 10.1002/1098-108x(198803)7:2<285::aid-eat2260070214>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Eating attitudes in college males

Abstract: Three hundred and forty male college students participated in a survey study of eating attitudes. Participants completed a survey including demographic data, a weight history, and the Eating Attitudes Test (EAT‐26). Twelve subjects or 3.5% of the population had elevated scores of 20 or above on the EAT‐26. Elevated scores correlated significantly with body building and with a past history of obesity. Fully 65% of the men reported weighing within 5 percentage points of their ideal weight. The authors suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…The number of significant differences found in men was clearly lower, and three out of four of these were in the opposite direction to those found in women. On the one hand, this result fits with the gender differences repeatedly found in the literature [41][42][43][44][45] . On the other hand, this result could be explained arguing that, perhaps, in men the cause of substance consumption is more social and, therefore, of a less ED-associated symptomatology.…”
Section: Discussionsupporting
confidence: 91%
“…The number of significant differences found in men was clearly lower, and three out of four of these were in the opposite direction to those found in women. On the one hand, this result fits with the gender differences repeatedly found in the literature [41][42][43][44][45] . On the other hand, this result could be explained arguing that, perhaps, in men the cause of substance consumption is more social and, therefore, of a less ED-associated symptomatology.…”
Section: Discussionsupporting
confidence: 91%
“…Many of the subscale items deal with binge eating behaviors, and 15- to 17-year-old boys commonly consume large amounts of food (Eiben, 2007; Katzman, Wolchik, & Braver, 1984). Males are also less likely to label the consumption of large quantities of food a binge or to report feeling out of control during the food consumption (Carlat & Camargo, 1991; Franco, Tamburino, Carroll, & Bernal, 1988; Lewinsohn et al, 2002). However, results from our measurement invariance analyses provide some limited evidence that this is not the case, as we constrained item-level thresholds to be equal; we did the same for factor loadings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that boys’ eating problems are undetected (Anderson & Bulik 2004). Boys are presumed to under‐report the problem because of the female stigma of ED (Franco et al. 1988) disordered eating is considered as specific to female gender (Anderson & Bulik 2004).…”
Section: Introductionmentioning
confidence: 99%